Improving Student-Teachers' Research Literacies through APA Citation 7th and Mendeley Workshops - Ani Pujiastuti; Yogi Saputra Mahmud; Muhammad Reyhan Andaffa; Nadine Evangelista; Kimberly Golda (Publikasi Pendidikan, 2021)
Academic honesty and plagiarism awareness become essential abilities for university students and early-career researchers. One way to enhance academic honesty and awareness of plagiarism issues is by mastering the skills of managing citations and references/bibliographies. Moreover, nowadays, various reference manager applications can be utilized to assist college students and early researchers in their research activities. Based on these statements, the Primary School Teacher Education (PSTE) study program and Center of Language and Culture (CLC) at President University conducted a community service program for university students and early researchers. This program was conducted through an online platform called Zoom as a preventive measure to curb the spread of the COVID-19 virus. There were 370 students, teachers, and early researchers from campuses across Indonesia and even overseas (Australia & China) who registered for this community service program. Based on the survey distributed after the program, the majority of participants responded very positively, in which their comprehension of referencing and citing and Mendeley is considered improving significantly. Some implications for future practice and research are also outlined in this article.